Elemental composition and health risk assessment of giant mudskipper Periophthalmodon schlosseri from the intertidal zone of the West Coast of Peninsular Malaysia - Looi, Ley Juen; Aris, Ahmad Zaharin; Mohd Isa, Noorain; Md. Yusoff, Fatimah; Haris, Hazzeman (Frontiers Media, 2021)
The elemental pollution in the intertidal zone of the West Coast of Peninsular Malaysia is of concern because this place is an ultimate sink of anthropogenic contaminants. In this study, the elemental concentrations (Al, Fe, Ba, Co, Cu, Cr, Mn, Ni, Pb, Zn, As, and Cd) in various tissues (muscle, gill, liver, gastrointestinal tract, and scale) of the giant mudskippers (Periophthalmodon schlosseri) from the West Coast of Peninsular Malaysia were determined by the inductively coupled plasma-mass spectrometry. The potential health risks associated with fish muscle consumption were assessed using estimated weekly intake (EWI), target hazard quotient (THQ), and target cancer risk (TR). The results showed that relatively high concentrations of Fe (1,641.91 ± 96.77 mg/kg), Ba (7.07 ± 0.05 mg/kg), Co (0.32 ± 0.00 mg/kg), Mn (36.08 ± 0.04 mg/kg), and Ni (4.43 ± 0.06 mg/kg) were found in the fish scales, suggesting the uptake waterborne elements via dermal exposure. However, all studied elements in the fish muscle were below the national and international food permissible limits. Health risk assessment through the estimation of THQ suggested that long-term exposure of As through fish consumption would cause possible non-carcinogenic risk. Also, the estimation of TR indicated that consumers are susceptible to cancer risks because of Cr and As exposure via fish consumption. Thus, for a developing country like Malaysia, it is recommended to include continuous monitoring of intertidal zones, using potential bioindicators, to assess ecosystem health status and safeguard human health. Additionally, mitigation strategies to address estuaries contamination and efforts to conserve and sustain natural resources should be established.